More trade, less diffusion: Technology transfers and the dynamic effects of import liberalization - Gustavo de Souza; Ruben Gaetani; Martí Mestieri (Federal Reserve Bank of Chicago, 2024)
How does international trade affect technology diffusion? We show that tariff increases in Brazil lead to more international technology transfers to Brazilian firms and more citations to foreign patents. The highest increase in citations occurs among firms located near those receiving technology transfers, and it is driven largely by citations to firms transferring technology to Brazil. These findings suggest that import tariffs can facilitate the diffusion of foreign technology by promoting technology transfers. We quantify this effect in a growth model that incorporates trade, technology transfers, and their effect on diffusion. When tariffs in Brazil rise, foreign firms transfer their technology rather than export their products, boosting the diffusion of foreign knowledge. An optimal subsidy to technology transfers significantly amplifies the welfare gains from trade liberalization.
Keywords: O33; O40; 330; technology diffusion; growth; technology transfers; international trade